Horae semiticae - Gibson, Margaret Dunlop; Lewis, Agnes Smith (C.J. Clay, 1903)
I. The Didascalia Apostolorum in Syriac / Margaret Dunlop Gibson. -- II. The Didascalia Apostolorum in English / Margaret Dunlop Gibson. -- III. Acta mythologica apostolorum / Agnes Smith Lewis. -- V.-VII, X-XI. The commentaries of Isho'dad of Merv ... / Edited and translated by Margaret Dunlop Gibson ; with an introduction by James Rendel Harris.-- VIII. Codex climaci rescriptus / Agnes Smith Lewis. -- IX. The forty martyrs of the Sinai Desert and the story of Eulogios / Agnes Smith Lewis.